Benthic–limnetic morphological variation in fishes: Dissolved organic carbon concentration produces unexpected patterns. Issue 3 (16th March 2022) - Bishop, Chelsea E.; Gahm, Kaija; Hendry, Andrew P.; Jones, Stuart E.; Stange, Madlen; Solomon, Christopher T.
Abstract: Variation in traits related to foraging and locomotion in benthic and limnetic habitats has been observed in many fishes. Benthic and limnetic food chain productivity in lakes is strongly influenced by the concentration of dissolved organic carbon (DOC) in the water, suggesting that DOC might indirectly impose selection on these traits and lead to classic benthic forms at low DOC concentrations and limnetic forms at high DOC concentrations. We tested this hypothesis via geometric morphometric and meristic analyses of bluegill sunfish ( Lepomis macrochirus, Centrarchidae) from 14 lakes with DOC concentrations ranging from 4 to 24 mg/L. These lakes, located in close proximity to each other, straddle the drainage divide between the Mississippi River and Laurentian Great Lakes basins in northern Wisconsin, USA. Bluegill morphology was consistently related to lake DOC concentration in both drainage basins, despite differences in morphology between basins. Fish from higher DOC lakes had deeper bodies and smaller heads, among other differences, though the proportion of shape variation described by DOC was low. Gill raker length and inter‐raker spacing were positively related to DOC concentration. Although some traits were thus related to DOC concentration, the directions of these relationships did not match the predicted benthic–limnetic patterns. Further, no relationships were evident between DOC and gill raker number, eye width, pectoral fin dimensions, or pectoral fin insertion angle in univariate analyses. These variable outcomes suggest that selection linked to DOC does not map neatly onto the classic benthic–limnetic axis, that high DOC favors a benthic–limnetic generalist rather than a limnetic specialist, or that the benthic–limnetic morphological dichotomy is less clear and universal than is often suggested.